URGENSI IJTIHAD SAINTIFIK DALAM MENJAWAB PROBLEMATIKA HUKUM TRANSAKSI KONTEMPORER - Mustaring, Mustaring (DIKTUM: Jurnal Syariah dan Hukum, 2010)
The article below traces to find the urgency of saintific ijtihad to solve Islamic law problems of contemporary transaction (muâamalah muâasirah) in the age of globalization. The age of globalization supported by information technologies revolusion makes all aspects of human life changes rapidly especially in economic activities. Many kinds and aspects of transaction that human did not think many years ago, occur in this era, for instance insurance, electronic banking, e-commerce, capital market, unit trust, etc. All forms of transaction in this era need to be solved and justified by Islamic law in order to all muslims in the world can participate in economic activities among other people at the global era. Islam as the last religion revealed by Allah swt. has many tools to anticipate and solve contemporary problems occurring in the global era. Alquran and al-Sunnah as the main sources of Islamic law provide tools to make Islamic teachings always suitable for all time, namely by saintific ijtihad. By doing saintific ijtihad to solve contemporary transaction problems in this global era will make Islamic law always appropriate whenever and wherever.